Population Status of Napoleon Wrasse (Cheilinus undulatus- Rüppell 1835) in Reef Waters of Banda Islands, Centre Molluccas Province - Suharti, Sasanti Retno; Edrus, Isa Nagib; Hermana, Indra Setiadi (Indonesian Fisheries Research Journal, 2023)
ABSTRACT Napoleon wrasse (Cheilinus undulatus) has been listed in Appendix II of  Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES). Under CITES regulations, countries exporting vulnerable species are required to guarantee any exports being not detrimental to the species survival in their ecosystem.The last state of wild population sizes and its exploitation level for this species in study area did not well documented. Population study of  Napoleon wrasse was undertaken in the Banda Waters of Centre Molluccas on October 2018. This study aims to identify the density and length frequency distribution of Napoleon wrasse population in Banda waters, with the intention of providing information about fishing intensity for the fish management. Method of the study used was Underwater Visual Census (UVC) to gather population data and also used Global Positioning System (GPS) to find out the length of area census.   Fish length (TL) was visually estimated using the stick method. The result shows there are 168 individual of Napoleon fish with sizes ranged from 10 to 90 cm TL. The population density of this species was 7.14 fish/ha within 23.5 hectars of UVC total areas and found more abundant of Napoleon wrasse in Ai Island waters. Length frequency distribution of the fish was dominated by fish of  40 cm in length (TL). Fish population in Banda waters indicated high density level with low fishing intensity.